(untitled) (Circe de clásicos y modernos, 2021)
Aurelius Prudentius Clemens is one of the most important Christian poets in Late Antiquity, whose work had a wide impact on the literary creations of the Middle Ages. In particular, the Psychomachia, an allegorical combatbetween Virtues and Vices, which combines the preceding epic tradition with Christian theology, constitutes the most representative poem of our poet. In this paper we will study the poetic strategies used by Prudentius in the proem of Psychomachia (v. 1-20), with the purpose that the tension between discursive materiality (form) and religious spirituality (content) will be analysed as an aesthetic feature that is accentuated, with greater intensity towards the end of the 5th century.